An exploration of the impact of museum architecture on the visitor experience and understanding of national identity - Alnunan, Maha (2023)
Minimal published research exists to date on the nature of Saudi Arabian national identity and its relationship with architecture. To address this, the present thesis focuses on the themes of nation-building and cultural heritage as lenses through which to study the concept of national identity as manifested in the architecture of Saudi Arabia. The central case-study involves a visitor-focused analysis of The Saudi National Museum (SNM), which was established in 1999 as part of the King Abdul-Aziz Historical Centre in the Saudi capital city, Riyadh. This study is motivated by two related research questions: (1), What do we mean by ‘national identity’, and to what extent does the Islamic religion inform this identity, in the case of Saudi Arabia? And (2) How does the architecture of the SNM express this identity, and how effectively does it contribute to strengthening it through the specific configuration of the visitor journey? The research begins with a review of prior literature examining the theoretical dimensions of the three key areas of study: identity, architecture, and museums. Related issues specific to the study of museums – such as narratives, exhibitions, and visitor behaviour, are also explored in depth in order to clarify their role in the construction of a sense of national identity in the context of Saudi Arabia. The review is limited to the period from the late 1930s to the present day, during which time Saudi Arabia underwent a major process of urbanisation, alongside additional significant social and political changes. The study focuses on the SNM, the architectural characteristics (including space, environment and exhibitions) which were evaluated through a combination of qualitative and quantitative methods. The application of the ‘scales of narrativity’ model, and two-communication denotative and connotative meanings were used as theoretical tools to afford insights into museum environments, as these are seen as effective vehicles for promoting identity, and emphasising the impact of architecture on the process of constructing meaning. The views of architects, designers and museum directors were also studied, and visitor experience surveys issued, in order to understand the relationship between the significant individual elements of the museum exhibition environment and the overarching narrative of the visitor journey. The visitor experience comprises influential, cognitive and behavioural aspects, which were analysed through a combination of self-reported responses to open-ended questions and observed visitor behaviour. Subsequently, the study revealed the impact of museum architecture on the expression of national identity to be more complex than previously assumed. Considering the matter of identity through empirical evidence from architects’ and museum directors’ views, provided a way of investigating the various paradigms of identity, showing how the participants translated and expressed overlapping and sometimes conflicting definitions. By comparing national identity and Islamic identity, alongside regional and local identity, a comprehensive finding of the thesis suggests the significance of religion in constituting and consolidating the performance of Saudi national identity. By evaluating the museum visitors’ experiences, the thesis also identifies how the architecture of the SNM building contributes significantly to the experience and understanding of the overall exhibition narrative. A strong correlation between the effectiveness of the architectural design and the exhibition design emerged throughout the SNM’s eight main exhibition spaces (in addition to the specific configuration of the overall visitor journey), strengthening the sense of Saudi national identity. This finding offers significant insights into the efficiency of museums in general as instrumental in the expression of national identity via exhibitions, architecture, and the narrative structure of the visitor journey.